1992
DOI: 10.1117/12.60371
|View full text |Cite
|
Sign up to set email alerts
|

<title>Video-microscopy of NCAP films: the observation of LC droplets in real time</title>

Abstract: We have used video-microscopy to observe the behavior of liquid crystal (LC) droplets within nematic droplet-polymer films (NCAP) as the droplets respond to an applied electric field. The textures observed at intermediate fields yielded information about the process of liquid crystal orientation dynamics within droplets.The nematic droplet-polymer films had low LC content (less than 1 percent) to allow the observation of individual droplets in a 2-6Rm size range. The aqueous emulsification technique was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The response of the LC no longer followed the change in the electric polarity 36, 42, 45–48. For a series‐connected dielectric composite model that is quite analogous to the present polymer/LC composite films, the applied electric field is not totally imposed on the LC phase but depends on the magnitude of the dielectric constants and the conductivity of the matrix polymer and LC 17, 37, 38. This partition of the external electric field to LC is given by eq.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The response of the LC no longer followed the change in the electric polarity 36, 42, 45–48. For a series‐connected dielectric composite model that is quite analogous to the present polymer/LC composite films, the applied electric field is not totally imposed on the LC phase but depends on the magnitude of the dielectric constants and the conductivity of the matrix polymer and LC 17, 37, 38. This partition of the external electric field to LC is given by eq.…”
Section: Resultsmentioning
confidence: 95%
“…The degree of the hysteresis was apparent in all cases of switching frequency from 50 HZ to 1 kHz. The basic reason for hysteresis in PDLC films has been the topic of several discussions 35–37. However, the phenomenon may be related to the mechanism of orientation of the LC droplet director,38 which may depend on the LC/polymer compatibility‐induced interfacial polarization process, which ultimately influences the distribution of the relaxation time 30.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that hysteresis might be due to the possible defect movement in a droplet. 2,38 Reamy et al 38 observed that hysteresis may be related to the mechanism of orientation of the droplet director, which ultimately may depend on the polymer/LC compatibility induced interfacial polymerization. We observed that DV 50 became less significant as the E7 content in PMMA increased.…”
Section: Electro-optical Responsesmentioning
confidence: 99%
“…The sources which give rise to hysteresis phenomenon have been studied by various researchers [117,135,138,140,141]. Hysteresis depends on the rate at which fields are applied and removed.…”
Section: Hysteresis Effectmentioning
confidence: 99%